2008
DOI: 10.4049/jimmunol.180.4.2069
|View full text |Cite
|
Sign up to set email alerts
|

pConsensus Peptide Induces Tolerogenic CD8+ T Cells in Lupus-Prone (NZB × NZW)F1 Mice by Differentially Regulating Foxp3 and PD1 Molecules

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease caused primarily by autoantibodies (including IgG anti‐DNA) and immune complexes. Tolerization with an artificial peptide (pCONSENSUS, pCons) based on murine anti‐DNA IgG sequences containing MHC class I and class II T cell determinants, lupus‐prone NZB/NZW F1 female (BWF1) mice develop regulatory CD4+CD25+T cells and inhibitory CD8+T cells, both of which suppress anti‐DNA Ig production and immune glomerulonephritis. In the present work, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
123
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(126 citation statements)
references
References 59 publications
2
123
1
Order By: Relevance
“…Table shows CD8 genes differentially expressed in naive vs pCons-treated mice We have long been interested in the role of CD8 þ T cells in murine lupus and in their specific role in the system of pCons-induced tolerance. 5,7,[24][25][26] The analysis of CD8 þ T cells from naive vs pCons-treated mice indicated that 60 genes were differentially expressed in this cell subset ( Figure 1a). Gene and condition clustering of CD8 þ T cells showed that large numbers of genes were downregulated in naive cells with higher expression in tolerized cells ( Figure 1a bottom two lines).…”
Section: Differential Gene Expression In Splenic Wbc From Naive Vs Pcmentioning
confidence: 99%
See 4 more Smart Citations
“…Table shows CD8 genes differentially expressed in naive vs pCons-treated mice We have long been interested in the role of CD8 þ T cells in murine lupus and in their specific role in the system of pCons-induced tolerance. 5,7,[24][25][26] The analysis of CD8 þ T cells from naive vs pCons-treated mice indicated that 60 genes were differentially expressed in this cell subset ( Figure 1a). Gene and condition clustering of CD8 þ T cells showed that large numbers of genes were downregulated in naive cells with higher expression in tolerized cells ( Figure 1a bottom two lines).…”
Section: Differential Gene Expression In Splenic Wbc From Naive Vs Pcmentioning
confidence: 99%
“…We have shown previously that interference with the expression of this gene via siRNA abrogated 60-70% of the suppressive capacity of the CD8 þ T cells from tolerized mice. 7,24,25 Silencing of one gene (Bcl2) in CD8 þ T cells from tolerized mice does not effect expression of other selected genes known to be involved (or not) in the suppressive capacity of CD8 þ Treg in our system To test whether silencing of bcl2 in tolerized CD8 þ T cells affects expression of other genes, we silenced tolerized CD8 þ T cells with different siRNA as described in the Materials and methods section and in the figure legends. Results shown in Figure 5 illustrate that silencing of bcl2 did not significantly affect the expression of other genes studied.…”
Section: Reproducibilitymentioning
confidence: 99%
See 3 more Smart Citations